Activities of the summer party of the 45th Japanese Antarctic Research Expedition in 2003-2004 - Hiroshi Kanda (National Institute of Polar Research, 2005)
The summer activities in the 2003-2004 austral summer of the 45th Japanese Antarctic Research Expedition (JARE-45) are reported. The JARE-45 consisted of 62 members including 22 members of the summer party and 40 members of the wintering party. Besides, two wintering members and 6 summer members companied the expedition as observers. The Antarctic research vessel (icebreaker) Shirase" reached the pack ice edge near Lutzow-Holm Bay on 14th December 2003 and anchored at Syowa Station on 24th December. Including light oil transported by pipe, and freight transported by snow vehicles and by helicopter, a total of 1107.2 t of cargo was transported. Construction of facilities at Syowa Station was carried out. The construction of an INTELSAT antenna and shelter continued throughout the summer at Syowa Station. Summer research programs included atmospheric observations, geodesy at Syowa Station, and geological and biological field surveys in ice-free areas along the Soya Coast and the Prince Olav Coast. All of the summer party left Syowa Station on 15th February and headed to Sydney, east Australia. En route, oceanography, marine biological observations and marine geomagnetism were carried out on board. Members of the summer party of JARE-45 returned to Narita on 27th March 2004. Transport of personnel to Dome Fuji Station by airplane via the Russian Antarctic Station, Novolazarevskaya was performed for the first time.